Group II Metabotropic Glutamate Receptors as Targets for Novel Antipsychotic Drugs - Muguruza, Carolina; Meana, J. Javier; Callado, Luis F. (Frontiers in Pharmacology, 2016)
Schizophrenia is a chronic psychiatric disorder which substantially impairs patients’ quality of life. Despite the extensive research in this field, the pathophysiology and aetiology of schizophrenia remain unknown. Different neurotransmitter systems and functional networks have been found to be affected in the brain of patients with schizophrenia. In this context, postmortem brain studies as well as genetic assays have suggested alterations in Group II metabotropic glutamate receptors (mGluRs) in schizophrenia. Despite many years of drug research, several needs in the treatment of schizophrenia have not been addressed sufficiently. In fact, only 5-10% of patients with schizophrenia successfully achieve a full recovery after treatment. In recent years mGluRs have turned up as novel targets for the design of new antipsychotic medications for schizophrenia. Concretely, Group II mGluRs are of particular interest due to their regulatory role in neurotransmission modulating glutamatergic activity in brain synapses. Preclinical studies have demonstrated that orthosteric Group II mGluR agonists exhibit antipsychotic-like properties in animal models of schizophrenia. However, when these compounds have been tested in human clinical studies with schizophrenic patients results have been inconclusive. Nevertheless, it has been recently suggested that this apparent lack of efficacy in schizophrenic patients may be related to previous exposure to atypical antipsychotics. Moreover, the role of the functional heterocomplex formed by 5-HT2A and mGlu2 receptors in the clinical response to Group II mGluR agonists is currently under study.